Exact Solutions for Nonclassical Stefan Problems - Adriana C. Briozzo; Domingo A. Tarzia (International Journal of Differential Equations)
We consider one-phase nonclassical unidimensional Stefan problems for a source function F which depends on the heat flux, or the temperature on the fixed face x=0. In the first case, we assume a temperature boundary condition, and in the second case we assume a heat flux boundary condition or a convective boundary condition at the fixed face. Exact solutions of a similarity type are obtained in all cases.